(untitled) (Revista de Ciências Agroveterinárias, 2022)
The Agricultural Research Company of Santa Catarina State (Epagri) is one of the main references in agricultural research. The objective of this paper was to make a bibliometric analysis of the scientific publications generated by Epagri, whose metadata are registered in the Epagri System of Technical and Scientific Production (Seprotec). The metadata year of publication, title, keywords, and publication type were considered in analysis. Metadata were analyzed in the statistical package R, using the UDPIPE library. From 1972 to October 2021, 15,841 publications were indexed in Seprotec, of which 67% as scientific publications. During the 70s and 80s, research focused on agronomic issues, seeking to increase crop productivity. From the 90s onwards, the environmental component gained relevance, addressing soil and water conservation aspects. Today, agricultural research in Santa Catarina is facing a new challenge, to make agricultural activity economically, socially and environmentally viable. Among the new research subjects, agroecology and regenerative agriculture stand out.